2016
DOI: 10.1371/journal.pone.0147029
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Hormonal Factors on the Risk of Developing Cervical Cancer and Pre-Cancer: Results from the EPIC Cohort

Abstract: BackgroundIn addition to HPV, high parity and hormonal contraceptives have been associated with cervical cancer (CC). However, most of the evidence comes from retrospective case-control studies. The aim of this study is to prospectively evaluate associations between hormonal factors and risk of developing cervical intraepithelial neoplasia grade 3 (CIN3)/carcinoma in situ (CIS) and invasive cervical cancer (ICC).Methods and FindingsWe followed a cohort of 308,036 women recruited in the European Prospective Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 38 publications
3
106
1
18
Order By: Relevance
“…There are between oral contraceptive use and risk of cervical cancer. The study conducted by Vaisy et al, (2014) and Roura et al, (2016) that the duration of oral contraceptive use have a risk three times more likely to have cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There are between oral contraceptive use and risk of cervical cancer. The study conducted by Vaisy et al, (2014) and Roura et al, (2016) that the duration of oral contraceptive use have a risk three times more likely to have cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the transformation zone of the uterine ectocervix, which serves as the site of initiation of tumorigenesis, is highly sensitive to steroid hormone stimulation (Remoue et al 2003). There is a consistent association between the degree of steroid hormone contraceptive usage, repeated fullterm pregnancies and HPV infection and an increased risk of developing CC (Moreno et al 2002, Muñoz et al 2002, Chung et al 2010, Marks et al 2011, Liao et al 2012, Roura et al 2016. Several investigators have shown that the mere presence of an HPV infection is not a mandate to develop CC.…”
Section: Role Of Endogenous and Exogenous Oestrogensmentioning
confidence: 99%
“…However, the role of oestrogens in human CC has not yet been well-defined (Chung et al 2010). Currently, with the epidemiological evidence linking multi-parity and oral contraceptive usage to an increase in CC risk, oestrogens have been speculated to be involved in the development of cervical carcinogenesis (Moreno et al 2002, Muñoz et al 2002, Roura et al 2016. Nevertheless, such carcinogenic transformations due to oestrogens are not physiological and involve a synergistic combination with infection of high-risk human papilloma virus (HPV) as the strongest factor (Brake & Lambert 2005, Chung et al 2008, Marks et al 2011, Liao et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The full evolving spectrum of infection of basal and squamous epithelial cells is intrinsically a parameter function of the proliferative activities of cells localized predominantly within the transformation zone between the os and the squamo-columnar cell junction. High parity and hormonal contraceptives have also been related to cervical cancer [12].…”
Section: Evolution Of Infectionmentioning
confidence: 99%